2004
DOI: 10.1172/jci21689
|View full text |Cite|
|
Sign up to set email alerts
|

A role for proteinase-activated receptor–1 in inflammatory bowel diseases

Abstract: Proteinase-activated receptor-1 (PAR 1 ), a G protein-coupled receptor activated by thrombin, is highly expressed in different cell types of the gastrointestinal tract. The activity of thrombin and of other proteinases is significantly increased in the colon of inflammatory bowel disease (IBD) patients. Since PAR 1 activation in tissues other than the gut provoked inflammation, we hypothesized that PAR 1 activation in the colon is involved in the pathogenesis of IBD. Here, we demonstrate that PAR 1 is overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(25 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…In the gastrointestinal (GI) tract, PARs can be activated by endogenous proteases secreted by the pancreas and mast cells, and potentially by the luminal enteric microbiota, resulting in permeability of the intestinal epithelium (49). Given that increased intestinal permeability is a hallmark of IBD and that PAR expression on the gut epithelium differs between IBD patients and healthy individuals (50,51), it is possible that these receptors are involved in enteric microbial protease-mediated permeability of the intestine. Although the activation of PAR1, -2, and -4 isoforms has been linked to intestinal permeability (25,52), increased intestinal permeability induced by PAR2 has been reported to occur via disruption of the tight junctions (T-Js) between epithelial cells (paracellular permeability).…”
Section: Discussionmentioning
confidence: 99%
“…In the gastrointestinal (GI) tract, PARs can be activated by endogenous proteases secreted by the pancreas and mast cells, and potentially by the luminal enteric microbiota, resulting in permeability of the intestinal epithelium (49). Given that increased intestinal permeability is a hallmark of IBD and that PAR expression on the gut epithelium differs between IBD patients and healthy individuals (50,51), it is possible that these receptors are involved in enteric microbial protease-mediated permeability of the intestine. Although the activation of PAR1, -2, and -4 isoforms has been linked to intestinal permeability (25,52), increased intestinal permeability induced by PAR2 has been reported to occur via disruption of the tight junctions (T-Js) between epithelial cells (paracellular permeability).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that, in addition to IGF-1 and insulin, IGF-1R can also be transactivated by several GPCRs, including thrombin (30,53), endothelin-1 and bombesin (54), and angiotensin II (31). Similar to NTR1 (17,18), other GPCRs, including the receptors for thrombin (55,56) and bombesin (57), are also shown to play dual roles in intestinal inflammation. Interestingly, these GPCRs also transactivate the EGFRs that stimulate MAPK activation, leading to cell proliferation (28,58).…”
Section: Discussionmentioning
confidence: 99%
“…Dextran sodium sulfate (DSS)-induced colitis is a well established experimental model of IBD used to study cytokine-triggered inflammation and injury in the colon (16,17) as well as other mechanisms of colitis such as thrombin-triggered pathways of inflammation (18). DSS colitis is characterized histologically by infiltration of inflammatory cells into the lamina propria, with lymphoid hyperplasia, focal crypt damage, and epithelial ulceration (16)(17)(18)(19).…”
mentioning
confidence: 99%
“…DSS colitis is characterized histologically by infiltration of inflammatory cells into the lamina propria, with lymphoid hyperplasia, focal crypt damage, and epithelial ulceration (16)(17)(18)(19). These pathological changes are thought to develop as a result of a barrier-destructive effect of DSS on the epithelium, subsequent phagocytosis of lamina propria cells, and production of cytokines (16)(17)(18)(19). Although the relationship of murine DSSinduced colitis to the human disease remains to be established, this widely used IBD model has a number of advantages, including simplicity, high degree of uniformity of the lesions, and leukocyte infiltration (19).…”
mentioning
confidence: 99%